Occurrence of Staphylococcus pseudintermedius in dogs and cats and their antibiotic resistance profiles - Mohamed, Mohamed Abdelrahman (2014)
Staphylococcus pseudintermedius is an emerging coagulase positive staphylococci and has now become a threat to animal health due to multidrug resistance with very limited therapeutic options particularly in small animals and it requires urgent action to control its spread. The organism is now recognised as a significant pathogen in veterinary medicine causing skin, ear and wound infections. To date, there has been no studies done on S.pseudintermedius in dogs and cats in Malaysia. The aims of this study were to determine the presence of S.pseudintermedius in dogs and cats, to assess their antibiotic susceptibility and to detect mecA and blaZ genes in the isolates. Swab samples were taken aseptically from 200 apparently healthy dogs and cats; the sites swabbed were nasal cavity, buccal cavity, rectum and perineal skin. The animals consisted of pet dogs and cats that were brought to the Universiti Veterinary Hospital (Universiti Putra Malaysia) and stray dogs and cats that were kept in an animal shelter. All samples were cultured on selective media, presumptively identified by biochemical tests and Staphylococcus spp were confirmed by PCR assay. The isolates were tested for antibiotic resistance using standard disc diffusion method. The total prevalence of S.pseudintermedius in this study was 11.5% (23/200), of which 22% (11/50) in stray cats, 18% (9/50) stray dogs, 6% (3/50) pet dogs and 0% in pet cats animals were found positive to S.pseudintermedius. Results showed that a high number of stray animals were colonized with S.pseudintermedius compared to pet animals; this may be due to high animal density in the shelter, in contact with animals from many sources and the unknown pathogen carriage status of the majority of animals. This study also revealed that nasal cavity is the best site for isolation of the organism (5.5%), followed by buccal cavity (3.5%), skin (2.5%) and rectum (2.5%) but the difference was statistically not significant. In the second part of the study, S.pseudintermedius were tested against 12 antibiotics. The isolates were 100% resistant to penicillin, erythromycin and tetracycline, while they showed 100% susceptible to oxacillin, amoxicillinclavulanic acid, gentamicin, chloramphenicol, vancomycin, ciprofloxacin, enrofloxacin, cephalexin and rifampicin. The third part of the study was carried out to detect the presence of mecA and blaZ genes that are responsible for the resistance to methicillin and penicillin, respectively. The blaZ gene which codes for β-lactamases production was found in all of the isolates that were resistant to penicillin but not to methicillin. The resistance to three antibiotics showed the isolates as multidrug resistant and poses a significant risk for choosing drug of choice for treatment that may limit therapeutic options. Although the prevalence is low compared to other studies, the presence of S.pseudintermedius in dogs and cats could be a potential source of zoonotic infection and it has been reported in veterinary personnel and pet owners. Therefore, it is recommended that contact with infected animals should be reduced, hand washing should be performed after animal contact and risk of transmission from animal to animal should be reduced in veterinary clinics. Antibiotic resistance is a global public health concern and the presence of resistant genes remains an important topic of public health debate, therefore, common mechanisms of staphylococcal antibiotic resistant must be understood clearly and management of resistances should be practised such as prudent antimicrobial usage, including routine treatment options must be based on culture and susceptibility data when suitable to decrease the impact of this problem. This study has provided an overview of S.pseudintermedius in stray and pet dogs and cats in Selangor, Malaysia. Although the prevalence is quite low, however, those handling dogs and cats need to take extra precaution. For a better understanding of S.pseudintermedius concerning pathogenesis and transmission, more studies on the prevalence and characterization of S.pseudintermedius isolated pet animals, from veterinary staff and pet owners are needed.